An Overview of Quality Audit: A Boon for Pharmaceutical Sector - Anita Patidar; Gurmeet S. Chhabra; Dinesh K. Mishra (International Journal of Pharma and Bio Sciences, 2022)
This review article covers a combination of aspects of the sole entity which defines the quality of products in the pharmaceutical sector. Quality audit is one of the essential elements of ISO 9001 quality system standards. It assures that an organization has distinctly defined a quality system to manufacture the quality products and work according to it. Concession or negotiation in quality of pharmaceutical products would directly impact the health of patients so audits are performed at specified time interval to ensure the quality as it is benefaction for the companies towards gaining loyalty from customers, maintain regulatory standards, long term revenue and profit. Regulatory bodies have their standard assessment tools termed Audits and Inspection, which reviews and evaluates various records, systems, and procedures followed in an organization. Most of the articles glorify that the quality audits mainly involve documented examinations and verification of all the processes and activities routinely performed, leading to ensure the required quality standards. The article is a result of a collection of data about the principles and objectives of quality audit and the benefits it provides to the respective firm by following the proper audit plan, procedures, corrective actions, and follow up making us aware of methods of gathering information for an audit, a brief knowledge of audit closure meetings, reports and basic criteria for selecting the auditor. Auditors play an important role to guarantee their organization’s consistency with pharmaceutical United States Food and Drug Administration and current Good Manufacturing Practices guidelines and other quality standards like ICH Q10. The article also describes the deficiencies occurring during and after the audit and a case study regarding the audit. The figures represented in the given article comprises the basic principles of audit, types of audits, steps of conducting an audit efficiently, audit management, and flow cycle of audit which gives an overall idea of the running of audit in a consistent manner to check the product meets the regulatory requirements, expected results and patient’s compliance.